Antiproliferative potential of the essential oil of Origanum majorana Linn. in melanoma cells and intracellular effects on neoplastic and non-neoplastic cells (Research, Society and Development, 2021)
The objectives of this study were to evaluate the intracellular activity of the essential oil of Origanum majorana (MARJ) in Madin Darby Bovine Kidney (MDBK) and murine metastatic melanoma (B16F10) and elucidate your chemical composition. Through flow cytometry parameters were analyzed membrane fluidity (F), reactive oxygen species (ROS), DNA fragmentation index (IFD), mitochondrial membrane potential (MMP), cell cycle, plasma membrane lipoperoxidation (LPO), cell viability, necrosis and apoptosis of cell lines treated with MARJ at concentrations of 0.25, 0.5 and 1 mg/mL for 24 hours. The composition of MARJ was determined by gas chromatography, and its major components were terpenes: hydrated cis-sabinene, 4-terpineol and gamma-terpinene. The results showed that all MARJ concentrations reduced ROS, LPO and S phase cells of the MDBK lineage. In B16F10 cells, MARJ treatments reduced ROS and cells in G2 phase, increasing cells in S phase. Concentrations of 0.5 and 1 mg/mL caused a reduction in F and 0.5 mg/mL increased the MMP in the MDBK lineage, while LPO was reduced at the concentration of 0.5 mg/mL in the B16F10 cells. The results of the evaluations of ROS production, plasma membrane integrity and LPO indicated antioxidant activity in the cells studied. Through cell cycle analysis, it was possible to observe that MARJ exerted an antiproliferative effect on melanoma cells, being able to interrupt the multiplication of this cell type.